2020
DOI: 10.1017/s0144686x19001624
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the friendship networks of older Black and Minority Ethnic people living in the United Kingdom

Abstract: Older Black and Minority Ethnic (BME) people living in the United Kingdom (UK) are vulnerable to the experiences of social isolation and loneliness. Despite this, it is widely assumed that they adhere to traditional family practices and living arrangements that protect them from social isolation and loneliness. Such assumptions are problematic and can reify family networks as the main area of research for older BME people to the detriment of friendship networks which are also crucial. However, few researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While the term ethnic minority conceals significant heterogeneity, evidence suggests important patterning of loneliness by ethnicity among the older adult population ( Salway et al, 2020 ; Victor et al, 2012 ), with Black older adults (henceforth BOAs) showing low levels of social connection and support ( Taylor & Nguyen, 2020 ). A UK study by Hayanga et al (2021) found that Black and Asian adults older than age 65 years are nearly twice as likely (9% and 7%, respectively) to report having no close friends compared to white and other ethnic older adults of the same age (4%). Another study in the US found that race significantly moderated the relationship between loneliness and depressive symptoms among BOAs ( Taylor & Nguyen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the term ethnic minority conceals significant heterogeneity, evidence suggests important patterning of loneliness by ethnicity among the older adult population ( Salway et al, 2020 ; Victor et al, 2012 ), with Black older adults (henceforth BOAs) showing low levels of social connection and support ( Taylor & Nguyen, 2020 ). A UK study by Hayanga et al (2021) found that Black and Asian adults older than age 65 years are nearly twice as likely (9% and 7%, respectively) to report having no close friends compared to white and other ethnic older adults of the same age (4%). Another study in the US found that race significantly moderated the relationship between loneliness and depressive symptoms among BOAs ( Taylor & Nguyen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further research and conclusions. Loneliness and social isolation are extremely complex phenomena 6 , and require a deep understanding and deliberative treatment that was beyond the remit of this rapid review. The risk of running unsuccessful interventions may be higher than many triallists appear to recognise, and a failure to ensure that the processes identified as important in effective interventions are incorporated into intervention design may have adverse impacts for older people, for example in heightening their feelings of alienation 68 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%